2018
DOI: 10.1126/sciadv.aao5031
|View full text |Cite
|
Sign up to set email alerts
|

Oxide-mediated recovery of field-effect mobility in plasma-treated MoS 2

Abstract: Time-controlled plasma treatment of MoS2 FETs improves carrier transport due to the presence of a two-dimensional oxide phase.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
96
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(107 citation statements)
references
References 62 publications
11
96
0
Order By: Relevance
“…Jadwiszczak et al [133] exposed mechanically exfoliated MoS 2 few-layers to an O 2 -Ar plasma (O 2 :Ar = 1:3) for 2-28 s. The frequency of the plasma was 13.52 MHz. An oxide phase was generated under the plasma exposure, changing the electrical conductivity and carrier mobility of the 2D materials.…”
Section: Combinationmentioning
confidence: 99%
“…Jadwiszczak et al [133] exposed mechanically exfoliated MoS 2 few-layers to an O 2 -Ar plasma (O 2 :Ar = 1:3) for 2-28 s. The frequency of the plasma was 13.52 MHz. An oxide phase was generated under the plasma exposure, changing the electrical conductivity and carrier mobility of the 2D materials.…”
Section: Combinationmentioning
confidence: 99%
“…29 With extensive chalcogen vacancy formation and subsequent oxidation, sub-stoichiometric MoO 3−x can exhibit metallic behavior since oxygen vacancies act as donor levels in MoO 3 . 30 In this work, cycles of hydrogen and atmospheric exposure (or oxygen plasma) are used to (1) create chalcogen vacancies in MoS 2 and then (2) oxidize the vacancies. MoS 2 is lithographically converted to MoO 3−x in a highly selective manner.…”
Section: Introductionmentioning
confidence: 99%
“…The XPS measurement identified that the synthesized WSe 2 and MoS 2 wires consist of semiconducting 2H phase without mixing with 1T phase . In the spectrum of Mo, we did not observe any distinct signal for the Mo 6+ 3d 3/2 orbital located between 234 and 238 eV, which would be associated with the presence of oxidization or selenization of Mo atoms . This suggests that the inner MoS 2 was not deteriorated during the thermal‐decomposition step for WSe 2 synthesis.…”
mentioning
confidence: 68%